PENERAPAN TAX PLANNING PPN DALAM PENGHEMATAN BEBAN CASH FLOW DI CV. MMM - Leo, Nora Dewi Lestari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out how the implementation of tax planning on the value added tax as themaximization of tax saving and cash flow management at CV MMM. The input tax and output tax is the basisfor the calculation of payable value added tax which led to a cash out for a company which affects the load of cashflow amount. A descriptive approach is applied in this research which is discussed in this thesis by usinganalysis and qualitative method. It can be concluded from the results of this research that the implementation oftax planning in purchasing the companyâs assets such as car, the implementation of tax planning on advertisingservices (infomedia), the implementation of tax planning on the telephone receipt as input tax, tax planning as ameans of controlling cash flow by delaying the reporting of input tax at different period has been proven toprovide a significant results of the saving and beneficial to the company. This indicates that tax planning can beone of alternatives in controlling the companyâs cash flow.Keywords : Tax planning, Tax saving maximization, Cash Flow Management, Input Tax, Output Tax